2020
DOI: 10.3390/rs12244188
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Divide Migration as a Response to Asymmetric Uplift: An Example from the Zhongtiao Shan, North China

Abstract: Previous numerical–analytical approaches have suggested that the main range divide prefers to migrate towards the high uplift flank in the asymmetric tectonic uplift pattern. However, natural examples recording these processes and further verifying the numerical simulations results, are still lacking. In this study, the landscape features, and the probable drainage evolution history of the Zhongtiao Shan, a roughly west-east trending, half-horst block on the southernmost tip of the Shanxi Graben System, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 66 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…higher uplift on the southern range) of the range has compelled the main divide to move southward, and now holds the main divide in a new condition of dynamic equilibrium (Figure 8). According to previous studies (Goren et al, 2014;Su et al, 2020), the Qinghai Nanshan will turn into a decaying topography when the asymmetric uplift eliminates. In the decaying topography pattern, the main divide will migrate northward and stop at the central part of the topography, and eventually reach a new balanced state.…”
Section: The Tectonically Active Qinghai Nanshanmentioning
confidence: 97%
See 1 more Smart Citation
“…higher uplift on the southern range) of the range has compelled the main divide to move southward, and now holds the main divide in a new condition of dynamic equilibrium (Figure 8). According to previous studies (Goren et al, 2014;Su et al, 2020), the Qinghai Nanshan will turn into a decaying topography when the asymmetric uplift eliminates. In the decaying topography pattern, the main divide will migrate northward and stop at the central part of the topography, and eventually reach a new balanced state.…”
Section: The Tectonically Active Qinghai Nanshanmentioning
confidence: 97%
“…On the other hand, the mobility of the main divide of a range could be a useful metric to reveal spatial variation of regional tectonic deformation (mainly driven by the activity of the thrust fault). It is because that spatial variation of uplift rates could lead to the migration of the divide to the high uplift rate flank (Forte & Whipple, 2018; Goren, Willett, Herman, & Braun, 2014; He et al, 2021; Su, Wang, Lu, & Xie, 2020). In this study, channel steepness and divide migration were analysed in the strike‐slip‐related secondary thrust mountain (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of an equilibrium state of balance between the incision and uplift rates, according to the stream power model, in which the slope exponent is generally larger than the area exponent, the longitudinal profile of a river in a basin being uplifted faster should be steeper than that in a basin being uplifted slower. Thus, based on this understanding, the position of the divide should be on the faster uplifted side of the geometric center of the land; that is, short steep rivers occur on the faster uplifted side, whereas long gentle rivers occur on the slower uplifted side [15]. In Sado Island, however, despite the faster uplift on the northwestern side than on the southeastern side, each main divide is located on the southeastern side of the geometric center of Osado and Kosado.…”
Section: Of 22mentioning
confidence: 99%
“…Previous studies reported that, in cases of asymmetric uplift, the main divide moved from a slower uplift basin to a faster uplift basin, and observed a linear correlation between the differences in erosion rate and the divide migration rate, eventually reaching a quasi-steady state during asymmetric uplift [10][11]13]. Although several recent studies on natural landforms affected by asymmetric uplift have been conducted to elucidate the history of landform formation processes along with divide migration [3,[14][15][16], further research is required for a deeper understanding of divide migration affected by asymmetry or heterogeneous uplift.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of landscape evolution laboratory experiment and numerical simulations was performed to study two dynamical settings: terrains emerging from a subdued topography in response to uniform uplift, followed by an uplift gradient in the form of tilting. We focus on tectonic tilting because (i) tilting is widely-documented in various tectonic settings (e.g., Farías et al, 2005;Jackson et al, 1998;Shikakura et al, 2011;Whittaker et al, 2008;Castelltort et al, 2012;He et al, 2019; 6 Su et al, 2020;Stewart, 1980;Densmore et al, 2005;Ellis et al, 1999;Stockli et al, 2003), and (ii) previous studies have shown that tectonic tilting induces main divide migration that changes basins' geometry (e.g., Willett et al, 2014;Goren et al, 2014;Whipple et al, 2017;Forte et al, 2015;He et al, 2019He et al, , 2021Shi et al, 2021;Shikakura et al, 2012).…”
Section: Introductionmentioning
confidence: 99%